Double Charge Exchange on Medium Mass Nuclei (2004)
ABSTRACT: We studied the double-charge-exchange reaction on 93Nb and 56Fe targets. The energy dependence of forward transition was calculated based on an optical model with the nuclear structure described in the pseudo-SU(4) model.